A case study to identify quality attributes relationships for web-based applications - Zulzalil, Hazura; Abd Ghani, Abdul Azim; Selamat, Mohd Hasan; Mahmod, Ramlan (2008)
Software quality is a complex concept containing a large number of quality criteria. These quality criteria are usually interactive where preference outcome of one criterion over another criterion is always influenced by the remaining criteria. However, to avoid complexity researchers always tend to construct independent criteria which causing some bias effect in evaluation. This paper presents a method to investigate and identify the relationships of quality criteria in the development of web-based applications (WBA). Experienced-based approach and an online survey were conducted to gather the intended relationships. The results have shown that there exist relationships and interaction between the quality attributes. These relationships will be used later on in the aggregation procedure for the evaluation of the WBA.